Feasibility of integrating robotic exoskeleton gait training in inpatient rehabilitation. (18th May 2020) - Swank, Chad; Sikka, Seema; Driver, Simon; Bennett, Monica; Callender, Librada
Abstract: Objective: Learning to walk is a major goal of inpatient rehabilitation and robotic exoskeletons may provide a new gait training approach. Our purpose was to determine the feasibility of integrating the Ekso Gait Training device into inpatient rehabilitation in a neurologic population. Design: Longitudinal cohort design and convenience sample including physical therapists trained to use the Ekso Bionics Ekso GT™ robotic exoskeleton or inpatients with stroke or SCI. Therapists completed a focus group and survey at baseline and 6 months after initial Ekso training. Patients completed a survey indicating their satisfaction with using the Ekso. Results: Twenty-five patients used the Ekso an average of 4.5 sessions during their 38.5-day rehabilitation stay. Survey and focus group feedback revealed that therapists encountered measurement difficulties with the Ekso and limited treatment time influencing effectiveness of usage. After 6 months, therapists reported an improvement in feasibility. Patients tolerated Ekso sessions well, without any complications or adverse incidents, and reported improved mobility post session. Conclusion: Integrating Ekso gait training into clinical practice was not seamless but appears feasible. Barriers were addressed within the rehabilitation team and received administrative support in a process lasting several months. Patients enjoyed walking in Ekso and felt secure within the device. Implications for rehabilitation: Integrating Ekso gait training into clinical practice during inpatient rehabilitation is feasible. Overcoming barriers to implementation required administrative support and clinician persistence over several months. Patients tolerated Ekso sessions well, without any complications or adverse incidents.